Anti-caking method and mixing process of phenolic resin grinding wheel molding material
Patent Information
- Application Number
- CN202410792166.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-19
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-06-19
AI Technical Summary
酚醛树脂砂轮成型料在高温高湿环境下容易结块,导致松散性差,影响砂轮组织均匀性和硬度,甚至导致裂纹和报废。
Adding an anti-caking agent, preferably an anionic surfactant such as Taikoo oil, to the phenolic resin grinding wheel forming material forms a hydrophobic film, inhibits the dissolution and condensation reaction of the phenolic resin powder, and delays the agglomeration time.
It effectively prolongs the looseness of phenolic resin grinding wheel molding material, avoids clumping, improves production efficiency, and does not affect the hardness and operating speed of the grinding wheel.
Smart Images

Figure BDA0004900420950000081
Abstract
Description
Technical Field
[0001] This invention relates to the field of abrasive and grinding wheel technology, specifically to a method and mixing process for preventing phenolic resin grinding wheel molding materials from caking. Background Technology
[0002] Organic abrasives are grinding tools that use polymer compounds as binders to bond abrasive grains together, forming a grinding tool with a certain strength and hardness. Phenolic resin grinding wheels belong to this category of organic abrasives. Phenolic resin grinding wheels are mainly used in the steel, automotive, bearing, railway, vehicle, shipbuilding, chemical, instrumentation, aerospace, building materials, and other machinery processing industries. They can also be used to process various non-metallic and metallic materials, such as wood, rubber, plastics, glass, ceramics, stone, copper, aluminum, cast iron, and steel, as well as cemented carbide, high-speed steel, titanium steel, and stainless steel. Furthermore, they are used in food processing, medicine, and geological exploration.
[0003] Phenolic resin is typically a high-molecular-weight polymer obtained by the condensation polymerization of phenol and formaldehyde under acidic or alkaline catalysis. Having undergone over 100 years of development, phenolic resin has become the most important resin binder in the superhard materials and abrasives industry. This is mainly due to the following characteristics: ① Low price: The raw materials for phenolic resin are inexpensive, the production process is simple and mature, and the investment in synthesis and processing equipment is low; ② Easy molding process: Molding of phenolic resin only requires heating and pressurization; ③ Excellent high-temperature resistance: Compared to epoxy resin, unsaturated polyester, and most thermosetting resins, as well as most thermoplastics, cured phenolic resin exhibits excellent heat resistance and a high char residue at high temperatures; ④ High strength of the cured product, especially its high-temperature strength, making it particularly suitable for organic abrasives; ⑤ Good chemical stability, strong acid resistance, and good corrosion resistance. However, phenolic resin also has disadvantages such as high brittleness, high shrinkage, poor alkali resistance, easy moisture absorption, and poor electrical properties.
[0004] In the production process of phenolic resin grinding wheels, the freshly mixed phenolic resin grinding wheel forming material particles have a thin film of dry phenolic resin powder on their outer surface, allowing the particles to separate and maintaining the looseness of the forming material. However, because the curing agent hexamethylenetetramine in the phenolic resin powder has a strong hygroscopic effect, and the phenolic resin liquid also has a strong dissolving ability for the phenolic resin powder, the phenolic resin powder on the outer surface of the forming material particles will dissolve within a certain period of time, causing the forming material to clump and lose its looseness. In summer, due to the high temperature and humidity, this phenomenon is more pronounced, and the forming material is more prone to clumping. Poor looseness of the forming material can lead to uneven grinding wheel structure, uneven hardness, and even cracks, ultimately resulting in the scrapping of the grinding wheel. Therefore, improving the looseness of phenolic resin grinding wheel forming materials has always been a research hotspot and direction. Summary of the Invention
[0005] The purpose of this invention is to provide a method and mixing process for preventing phenolic resin grinding wheel molding material from caking, so as to solve the problems mentioned in the background art.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] A method for preventing caking of phenolic resin grinding wheel molding material involves adding an anti-caking agent to the molding material, comprising the following components by weight fraction: 100 parts abrasive, 3-4 parts phenolic resin liquid, 7-8 parts phenolic resin powder, 4 parts filler, and 0.5-2 parts anti-caking agent.
[0008] As a further preferred embodiment of the present invention, the anti-caking agent is an anionic surfactant that can form a uniform hydrophobic film on the surface of the abrasive, preventing hexamethylenetetramine in the phenolic resin powder from contacting moisture in the air, inhibiting the dissolution of the powdered phenolic resin, and reducing the activity of hydroxymethyl groups in the phenolic resin, thereby reducing the rate of condensation reaction between hydroxymethyl groups and hydrogen atoms and delaying the formation of a network cross-linked structure.
[0009] As a further preferred embodiment of the present invention, the anti-caking agent is Taikoo oil.
[0010] As a further preferred embodiment of the present invention, the amount of the anti-caking agent added is 0.5% to 2% of the mass of the abrasive.
[0011] As a further preferred embodiment of the present invention, the phenolic resin liquid is a wetting agent and the phenolic resin powder is a binder.
[0012] As a further preferred embodiment of the present invention, the abrasive is one or more of garnet, brown fused alumina, white fused alumina, black silicon carbide, and green silicon carbide.
[0013] As a further preferred embodiment of the present invention, the particle size range of the abrasive is F16#~F320#.
[0014] As a further preferred embodiment of the present invention, the filler is gypsum powder.
[0015] A process for preventing caking and mixing of phenolic resin grinding wheel forming material, applied to the above method, includes the following steps:
[0016] S1. Pour the abrasive and phenolic resin liquid into the mixer and mix for 450 seconds.
[0017] S2. Pour the wetted abrasive into the mixer, which has 50% of the filler mass at the bottom, and mix for 60 seconds.
[0018] S3. Pour the phenolic resin powder and the remaining 50% of the filler into the mixer and mix for 150 seconds.
[0019] S4. Add the anti-caking agent to the mixer and mix for 90 seconds.
[0020] S5. Use the mixed molding material after passing it through a sieve with a suitable mesh size.
[0021] As a further preferred embodiment of the present invention, the well-mixed molding material can maintain good looseness within 12 hours. During the grinding process, the molding material does not clump and can be used without further sieving.
[0022] Compared with the prior art, the beneficial effects of the present invention are:
[0023] The phenolic resin anti-caking agent of this invention, when applied to the mixing process of phenolic resin grinding wheels, can form a uniform hydrophobic film on the abrasive surface, preventing hexamethylenetetramine from contacting moisture in the air, inhibiting the dissolution of powdered phenolic resin, and reducing the activity of hydroxymethyl groups in the phenolic resin. This slows down the condensation reaction rate of hydroxymethyl groups with hydrogen atoms, delaying the formation of a network cross-linked structure. The anti-caking method of this invention can effectively extend the agglomeration time of the phenolic resin grinding wheel molding material, allowing it to remain in a loose state for a long time after mixing, eliminating the need for further sieving and facilitating subsequent grinding wheel pressing steps, thus greatly improving production efficiency. The mixing process described in this invention does not reduce the hardness, tensile strength, or operating speed of the grinding wheel. Detailed Implementation
[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] The technical solution of the present invention will be described in detail below with reference to specific embodiments. These specific embodiments can be combined with each other, and the same or similar concepts or processes may not be described again in some embodiments.
[0026] A method for preventing caking of phenolic resin grinding wheel molding material involves adding an anti-caking agent to the molding material, comprising the following components by weight fraction: 100 parts abrasive, 3-4 parts phenolic resin liquid, 7-8 parts phenolic resin powder, 4 parts filler, and 0.5-2 parts anti-caking agent.
[0027] The anti-caking agent is an anionic surfactant that can form a uniform hydrophobic film on the surface of the abrasive, preventing hexamethylenetetramine in the phenolic resin powder from contacting moisture in the air, inhibiting the dissolution of the powdered phenolic resin, and reducing the activity of hydroxymethyl groups in the phenolic resin, thereby slowing down the condensation reaction rate of hydroxymethyl groups with hydrogen atoms and delaying the formation of a network cross-linked structure. The anti-caking agent is terephthalic acid oil, and the amount of the anti-caking agent added is 0.5% to 2% of the mass of the abrasive. The phenolic resin liquid is a wetting agent, the phenolic resin powder is a binder, the abrasive is garnet, and the filler is gypsum powder.
[0028] A mixing process for preventing caking of phenolic resin grinding wheel molding material, the process comprising the following steps:
[0029] S1. Pour the abrasive and phenolic resin liquid into the mixer and mix for 450 seconds.
[0030] S2. Pour the wetted abrasive into the mixer, which has 50% of the filler mass at the bottom, and mix for 60 seconds.
[0031] S3. Pour the phenolic resin powder and the remaining 50% of the filler into the mixer and mix for 150 seconds.
[0032] S4. Add the anti-caking agent to the mixer and mix for 90 seconds.
[0033] S5. Use the mixed molding material after passing it through a sieve with a suitable mesh size.
[0034] Example 1
[0035] Mix 4000g of F80# garnet abrasive and 160g of phenolic resin liquid in a mixer for 450 seconds, then pour it into another mixer with 80g of gypsum powder at the bottom and mix for 60 seconds. Next, pour 310g of phenolic resin powder and 80g of gypsum powder into the mixer and mix for 150 seconds. Finally, add 40g of Taikoo oil and mix for 90 seconds. Pass the mixed molding material through an 8# sieve for later use.
[0036] The mixed molding material can maintain good looseness within 12 hours. During the grinding process, the molding material does not clump and can be used without further sieving, which greatly improves production efficiency.
[0037] Weigh out 137.5g of molding material that has been left to stand for 6 hours and press it into a volume of 72cm³. 3 Its density is 1.91 g / cm³. 3 The figure-eight block; 1156g of molding material that had been left to stand for 6 hours was weighed and pressed into a volume of 605.6cm³. 3 Its density is 1.91 g / cm³. 3A 200×20×38 (diameter×thickness×aperture) grinding wheel was used. The figure-eight blocks and the grinding wheel were hardened according to the curing process. After the surface of the figure-eight blocks and the grinding wheel was polished, the hardness, tensile strength and grinding wheel rotation strength were tested.
[0038] The test results are as follows: the hardness of the figure-eight block on both sides is 4.32 and 4.43 respectively; the tensile strength of the figure-eight block is 2.52 MPa; the grinding wheel is normal at a speed of 65 m / s, which meets the usage speed of 50 m / s.
[0039] Example 2
[0040] Mix 4000g of F80# garnet abrasive and 140g of phenolic resin liquid in a mixer for 450 seconds, then pour it into another mixer with 80g of gypsum powder at the bottom and mix for 60 seconds. Next, pour 320g of phenolic resin powder and 80g of gypsum powder into the mixer and mix for 150 seconds. Finally, add 50g of Taikoo oil and mix for 90 seconds. Pass the mixed molding material through an 8# sieve for later use.
[0041] The mixed molding material can maintain good looseness within 12 hours. During the grinding process, the molding material does not clump and can be used without further sieving, which greatly improves production efficiency.
[0042] Weigh out 137.5g of molding material that has been left to stand for 6 hours and press it into a volume of 72cm³. 3 Its density is 1.91 g / cm³. 3 The figure-eight block; 1156g of molding material that had been left to stand for 6 hours was weighed and pressed into a volume of 605.6cm³. 3 Its density is 1.91 g / cm³. 3 A 200×20×38 (diameter×thickness×aperture) grinding wheel was used. The figure-eight blocks and the grinding wheel were hardened according to the curing process. After the surface of the figure-eight blocks and the grinding wheel was polished, the hardness, tensile strength and grinding wheel rotation strength were tested.
[0043] The test results are as follows: the hardness of the figure-eight block on both sides is 4.26 and 4.38 respectively; the tensile strength of the figure-eight block is 2.72 MPa; the grinding wheel is normal at a speed of 65 m / s, which meets the usage speed of 50 m / s.
[0044] Example 3
[0045] Mix 4000g of F80# garnet abrasive and 120g of phenolic resin liquid in a mixer for 450 seconds, then pour it into another mixer with 80g of gypsum powder at the bottom and mix for 60 seconds. Next, pour 280g of phenolic resin powder and 80g of gypsum powder into the mixer and mix for 150 seconds. Finally, add 20g of Taikoo oil and mix for 90 seconds. Pass the mixed molding material through an 8# sieve for later use.
[0046] The mixed molding material can maintain relatively looseness within 12 hours. During the grinding process, the molding material does not clump significantly and can be used without further sieving, thus improving production efficiency.
[0047] Weigh out 137.5g of molding material that has been left to stand for 6 hours and press it into a volume of 72cm³. 3 Its density is 1.91 g / cm³. 3 The figure-eight block; 1156g of molding material that had been left to stand for 6 hours was weighed and pressed into a volume of 605.6cm³. 3 Its density is 1.91 g / cm³. 3 A 200×20×38 (diameter×thickness×aperture) grinding wheel was used. The figure-eight blocks and the grinding wheel were hardened according to the curing process. After the surface of the figure-eight blocks and the grinding wheel was polished, the hardness, tensile strength and grinding wheel rotation strength were tested.
[0048] The test results are as follows: the hardness of the figure-eight block on both sides is 4.12 and 4.23 respectively; the tensile strength of the figure-eight block is 2.32 MPa; the grinding wheel is normal at a speed of 65 m / s, which meets the usage speed of 50 m / s.
[0049] Example 4
[0050] Mix 4000g of F80# garnet abrasive and 120g of phenolic resin liquid in a mixer for 450 seconds, then pour it into another mixer with 80g of gypsum powder at the bottom and mix for 60 seconds. Next, pour 280g of phenolic resin powder and 80g of gypsum powder into the mixer and mix for 150 seconds. Finally, add 30g of Taikoo oil and mix for 90 seconds. Pass the mixed molding material through an 8# sieve for later use.
[0051] The mixed molding material can maintain its general looseness within 12 hours. During the grinding process, the molding material does not clump significantly and can be used without further sieving, thus improving production efficiency.
[0052] Weigh out 137.5g of molding material that has been left to stand for 6 hours and press it into a volume of 72cm³. 3 Its density is 1.91 g / cm³. 3 The figure-eight block; 1156g of molding material that had been left to stand for 6 hours was weighed and pressed into a volume of 605.6cm³. 3 Its density is 1.91 g / cm³. 3 A 200×20×38 (diameter×thickness×aperture) grinding wheel was used. The figure-eight blocks and the grinding wheel were hardened according to the curing process. After the surface of the figure-eight blocks and the grinding wheel was polished, the hardness, tensile strength and grinding wheel rotation strength were tested.
[0053] The test results are as follows: the hardness of the figure-eight block on both sides is 4.19 and 4.30 respectively; the tensile strength of the figure-eight block is 2.42 MPa; the grinding wheel is normal at a speed of 65 m / s, which meets the usage speed of 50 m / s.
[0054] Comparative Example 1
[0055] Mix 4000g of F80# garnet abrasive and 160g of phenolic resin liquid in a mixer for 450 seconds, then pour it into another mixer with 80g of gypsum powder at the bottom and mix for 60 seconds. Then pour 310g of phenolic resin powder and 80g of gypsum powder into the mixer and mix for 150 seconds. Pass the mixed molding material through an 8# sieve for later use.
[0056] After 1 hour, the mixed molding material becomes less loose and clumps together, requiring it to be sieved again before it can be pressed with a grinding wheel.
[0057] After the molding material was left to stand for 1 hour, it was passed through an 8# sieve again. 137.5g of the molding material was then weighed and pressed into a volume of 72cm³. 3 Its density is 1.91 g / cm³. 3 The figure-eight blocks; weigh 1156g of the material, pass it through an 8# sieve again, and press it into a mold with a volume of 605.6cm³. 3 Its density is 1.91 g / cm³. 3 A 200×20×38 (diameter×thickness×aperture) grinding wheel was used. The figure-eight blocks and the grinding wheel were hardened according to the curing process. After the surface of the figure-eight blocks and the grinding wheel was polished, the hardness, tensile strength and grinding wheel rotation strength were tested.
[0058] The test results are as follows: the hardness of the figure-eight block on both sides is 4.48 and 4.52 respectively; the tensile strength of the figure-eight block is 1.90 MPa; the grinding wheel operates normally at a speed of 65 m / s, which meets the usage speed of 50 m / s.
[0059] Comparative Example 2
[0060] Mix 4000g of F80# garnet abrasive and 160g of phenolic resin liquid in a mixer for 450 seconds, then pour it into another mixer with 80g of gypsum powder at the bottom and mix for 60 seconds. Next, pour 310g of phenolic resin powder and 80g of gypsum powder into the mixer and mix for 150 seconds. Finally, add 10g of Taikoo oil and mix for 90 seconds. Pass the mixed molding material through an 8# sieve for later use.
[0061] The mixed molding material can maintain good looseness for 2 hours, but after 2 hours the looseness deteriorates and clumping occurs.
[0062] After the molding material was left to stand for 2 hours, it was passed through an 8# sieve again. 137.5g of the molding material was then weighed and pressed into a volume of 72cm³. 3 Its density is 1.91 g / cm³.3 The figure-eight blocks; weigh 1156g of the material, pass it through an 8# sieve again, and press it into a mold with a volume of 605.6cm³. 3 Its density is 1.91 g / cm³. 3 A 200×20×38 (diameter×thickness×aperture) grinding wheel was used. The figure-eight blocks and the grinding wheel were hardened according to the curing process. After the surface of the figure-eight blocks and the grinding wheel was polished, the hardness, tensile strength and grinding wheel rotation strength were tested.
[0063] The test results are as follows: the hardness of the figure-eight block on both sides is 4.39 and 4.47 respectively; the tensile strength of the figure-eight block is 2.25 MPa; the grinding wheel operates normally at a speed of 65 m / s, which meets the usage speed of 50 m / s.
[0064] Table 1 Comparison of parameters for phenolic resin grinding wheel forming materials
[0065]
[0066] As can be seen from Examples 1, 2, 3, 4, Comparative Example 1, and Comparative Example 2, the addition of the anti-caking agent Taikoo oil can effectively improve the looseness of the phenolic resin grinding wheel molding material, prolong the agglomeration time of the molding material, and provide sufficient time for grinding wheel pressing, thus effectively improving production efficiency. Furthermore, the addition of the anti-caking agent Taikoo oil did not reduce the hardness, tensile strength, or operating speed of the grinding wheel. However, when the amount of anti-caking agent Taikoo oil added is less than 0.5% of the abrasive mass, the improvement in the looseness of the phenolic resin grinding wheel molding material is not very significant.
[0067] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preventing caking of phenolic resin grinding wheel molding material, characterized in that, An anti-caking agent is added to the molding material, comprising the following components by weight fraction: 100 parts abrasive, 3-4 parts phenolic resin liquid, 7-8 parts phenolic resin powder, 4 parts filler, and 0.5-2 parts anti-caking agent. The anti-caking agent is an anionic surfactant that can form a uniform hydrophobic film on the surface of the abrasive, preventing hexamethylenetetramine in the phenolic resin powder from contacting moisture in the air, inhibiting the dissolution of the powdered phenolic resin, and reducing the activity of hydroxymethyl groups in the phenolic resin, thereby slowing down the condensation reaction rate of hydroxymethyl groups with hydrogen atoms and delaying the formation of a network cross-linked structure. The anti-caking agent is terephthalic acid oil; the phenolic resin liquid is a wetting agent; the phenolic resin powder is a binder; the abrasive is garnet; and the filler is gypsum powder. The amount of the anti-caking agent added is 0.5% to 2% of the mass of the abrasive; The anti-caking mixing process for phenolic resin grinding wheel forming materials includes the following steps: S1. Pour the abrasive and phenolic resin liquid into the mixer and mix for 450 seconds. S2. Pour the wetted abrasive into the mixer, which has 50% of the filler mass at the bottom, and mix for 60 seconds. S3. Pour the phenolic resin powder and the remaining 50% of the filler into the mixer and mix for 150 seconds. S4. Add the anti-caking agent to the mixer and mix for 90 seconds. S5. Use the mixed molding material after passing it through an 8# sieve.
2. The method for preventing caking of phenolic resin grinding wheel molding material according to claim 1, characterized in that, The mixed molding material can maintain good looseness within 12 hours. During the grinding process, the molding material does not clump and can be used without further sieving.
Citation Information
Patent Citations
Application of vegetable fat in resin grinding wheel
CN104985538A
